Preventing infections in immunocompromised patients with kidney diseases: vaccines and antimicrobial prophylaxis - BERKE MENTEŞE, İLAY (My University, 2023)
The coronavirus disease 2019 (COVID-19) pandemic revealed that our understanding of infectious complications and strategies to mitigate severe infections in patients with glomerular diseases is limited. Beyond COVID-19, there are several infections that specifically impact care of patients receiving immunosuppressive measures. This review will provide an overview of six different infectious complications frequently encountered in patients with glomerular diseases, and will focus on recent achievements in terms of vaccine developments and understanding of the use of specific antimicrobial prophylaxis. These include influenza virus, Streptococcus pneumoniae, reactivation of a chronic or past infection with hepatitis B virus in cases receiving B-cell depletion, reactivation of cytomegalovirus, and cases of Pneumocystis jirovecii pneumonia in patients with anti-neutrophil cytoplasmic antibody-associated vasculitis. Varicella zoster virus infections are particularly frequent in patients with systemic lupus erythematosus and an inactivated vaccine is available to use as an alternative to the attenuated vaccine in patients receiving immunosuppressants. As with COVID-19 vaccines, vaccine responses are generally impaired in older patients, and after recent administration of B-cell depleting agents, and high doses of mycophenolate mofetil and other immunosuppressants. Strategies to curb infectious complications are manifold and will be outlined in this review.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Nephrology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ÜROLOJİ VE NEFROLOJİ; TRANSPLANTASYON; Clinical Medicine (MED); CLINICAL MEDICINE; UROLOGY & NEPHROLOGY; TRANSPLANTATION; Transplantasyon; Transplantation; glomerulonephritis; immunosuppression; infections; prophylaxis; vaccines